Should we redifine Hypertensive response in stress test to better predict cardiovascular risk?. (11th May 2021) - Silverio Antonio, P; Alves Da Silva, P; Valente Silva, J; Brito, J; Rodrigues, T; Couto Pereira, S; Cunha, N; Santos, R; Rigueira, J; Aguiar-Ricardo, I; David, D; J Pinto, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Systolic blood pressure (SBP) rise during exercise is normal, but some patients present with hypertensive response to exercise (HRE). The clinical implication of such phenomenon is not fully elucidated, and treatment strategies are still uncertain. Purpose: To evaluate the relationship between HRE and the development of major cardiovascular events (MACE) - death, acute coronary syndrome (ACS) and stroke. Methods: Single-center retrospective study of consecutive patients submitted to exercise test (ET) from 2012 to 2015. Patient's demographics, baseline clinical characteristics, vital signs during ET and MACE occurrence during follow-up were analysed. HRE was defined as a peak systolic blood pressure (PSBP) >210 mmHg in men and >190 mmHg in women, or a rise of the SBP of 60 mmHg in men or 50 mmHg in women or as a diastolic blood pressure >90 mmHg or a rise of 10 mmHg. Results: We included 458 patients with HRE (76% men, 57.5 ± 10.83 years). The most frequent comorbidities were hypertension (83%) and dyslipidaemia (61%). During a mean follow-up of 60 ± 2 months, the incidence of MACE was 9.2% with ACS being the most frequent (4.2%), followed by mortality (3.8%) and stroke (2.1%). Patients with inconclusive ET had a fourfold higher risk of acute coronary events (OR 4.1, CI 95% 1.55-11.14, p = 0.005). Baseline SBP and PSBP were predictors of MACE occurrence (OR 1.022, CI 95% 1.004-1.04, p = 0.016, OR 1.031 CI 95% 1.012-1.051, p = 0.001, respectively) and were both associated with cardiovascular hospitalization (p = 0.006; p < 0.001, respectively). PSBP had moderate ability to predict hospitalization of cardiovascular (CV) cause (AUC 0.71, p < 0.001) with a cut-off of 193 mmHg (sensibility 91%, specify 40%) and had moderate ability to predict MACE (AUC 0.67, p < 0.001) with a cut-off of 198 mmHg (sensibility 78.6%, specify 46.1%). Regarding mortality, antihypertensive therapy prior to ET was protective (p = 0.042), with no difference between different classes of drugs. Conclusion: Our data reveal a high rate of MACE occurrence between patients with HRE. The finding of diagnosed hypertension as a protective factor of stroke may be explained by the cardioprotective effect of antihypertensive drugs. An increased risk of ACS between patients with an inconclusive ET should lead to consider then for further investigation. HRE should be considered as part of CV risk assessment and adjusted lower HRE cut-off values should be considered in order to better predict MACE occurrence, particularly in high risk patients.